PENGARUH GEL EKSTRAK DAUN AKASIA (Acacia auriculiformis) TERHADAP PROSES PENYEMBUHAN LUKA SAYAT PADA MENCIT (Mus musculus) - Sriyanti Aoetpah; Alan Ch. Sabuna; Sonya Titin Nge (JURNAL KAJIAN VETERINER, 2019)
Acacia plant (Acacia auriculiformis) contains chemical compounds they are saponin, tanin and flavonoid. These compounds potentially in healing cut. This research used acacia leaf extract (Acacia auriculiformis) making in form of gel for the process of wound healing cut on mouse (Mus musculus). The purpose of this research are to know the influences of extract gel acacia leaf (Acacia auriculiformis) and to know the optimum concentracion extract gel acacia leaf that affective in wound healing cut on mouse (Mus musculus). Concentration variation of extract acacia leaf are 7%, 9% and 11%. The method used in research is experimental method with the complete random desing (CRD). Physical test supply gel that doing including pH test and homogenitas. Effective test gel in healing cut doing on 15 mice which separated became three treatments and two controls. Each treatment and control contains three mice which get cut with size 1,5 cm. The first treatment give 7% gel cocentration, the second treatment give 9% gel concentration, the first treatment give 11%, negative control give base gel and positive control give bioplacenton. Data analyze used Anova test one way and continue test LSD. Research result showed that extract gel acacia leaf with concentration variation 7%, 9% and 11% fulfill physic test gel supply that are pH test and homogenitas. Analysis result Anova one way showed that extract gel acacia leaf (Acacia auriculiformis) influence in the process of wound healing cuts on miouse (mus musculus). Based on the continue test LSD then known optimum concentration extract gel acacia leaf (Acacia auriculiformis) that effective of wound healing cuts on mouse (Mus musculus) that are 11%.